Research on the dynamics of changes in the sight-aesthetic quality of rural lake district landscapes in the aspect of implementing the European Landscape Convention - Senetra, Adam (International Conference “Environmental Engineering”, 2017)
The article presents selected methodological assumptions of developing and evaluating landscape attribute maps that could be used in the process of the implementation of the European Landscape Convention (ELC). The Convention led to the passing of the Act of 24th April 2015 on the modification of some acts due to the enhancement of landscape protection tools. Article 7 implements changes in the Act of 23rd March 2003 on spatial planning and land use management. Determining general rules for landscape auditing and defining the priority landscape are elements of the changes. On 11th September 2015, the regulations that partially carry out the recommendation of the Convention entered into force. The regulations oblige local governments to conduct landscape auditing (not less often than every 20 years). The article presents a new method for evaluating the aesthetic-scenic value of landscape (EEVL), developed by the author on the basis of conceptual works done between 2004 and 2008. Tests of this method started in 2008. Then an assessment of the aesthetic value of the municipality of Pozezdrze in the Masurian Lake District was made. The three measurements, collected in 2008, 2012 and 2016, were then used in comparing the dynamics of landscape transformations considering the aesthetic value over 8 years. The research enabled the assessment of the usefulness of the method in landscape auditing.
Keywords: landscape auditing; landscape protection; sight esthetic quality; point valuation